Genetic basis of variation in thermal developmental plasticity for Drosophila melanogaster body pigmentation - Lafuente, E. (2024)
Seasonal differences in insect pigmentation are attributed to the influence of ambient temperature on pigmentation development. This thermal plasticity is adaptive and heritable, and thereby capable of evolving. However, the specific genes contributing to the variation in plasticity that can drive its evolution remain largely unknown. To address this, we analysed pigmentation and pigmentation plasticity in Drosophila melanogaster. We measured two components of pigmentation in the thorax and abdomen: overall darkness and the proportion of length covered by darker pattern elements (a trident in the thorax and bands in the abdomen) in females from two developmental temperatures (17 or 28°C) and 191 genotypes. Using a GWAS approach to identify the genetic basis of variation in pigmentation and its response to temperature, we identified numerous dispersed QTLs, including some mapping to melanogenesis genes (yellow, ebony, and tan). Remarkably, we observed limited overlap between QTLs for variation within specific temperatures and those influencing thermal plasticity, as well as minimal overlap between plasticity QTLs across pigmentation components and across body parts. For most traits, consistent with selection favouring the retention of plasticity, we found that lower plasticity alleles were often at lower frequencies. The functional analysis of selected candidate QTLs and pigmentation genes largely confirmed their contributions to variation in pigmentation and/or pigmentation plasticity. Overall, our study reveals the existence and underlying basis of extensive and trait-specific genetic variation for pigmentation and pigmentation plasticity, offering a rich reservoir of raw material for natural selection to shape the evolution of these traits independently.